PENGARUH PERTUMBUHAN EKONOMI, INFLASI, DAN JUMLAH INDUSTRI TERHADAP KESEMPATAN KERJA DI KABUPATEN BONE BOLANGO - Harijono H. Imbran; Jamal Pratama Putra Nento (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2021)
Economic growth, inflation, and employment are indicators that affect employment opportunities and opportunities. The more job opportunities in an area will be able to have a positive impact on the economy in that area. This study aims to analyze the effect of economic growth, inflation and labor on employment opportunities in Bone Bolango Regency. This study uses a quantitative research approach with a 5-year secondary data base (2015-2019) and by using multiple linear regression analysis.The results showed that based on the results of research tests using multiple linear regression analysis techniques, it can be stated that there is a significant effect of the independent variables, namely economic growth, inflation rate, and employment in Bone Bolango Regency on employment. The multiple regression equation formed is: Y = -5.287 + 2.854X1 – 3.833X2 – 2.019X3 illustrates if there is an influence of economic growth, inflation, and labor on the absorption of labor in Bone Bolango Regency.